PERAN TARIAN GAWI SEBAGAI KEARIFAN LOKAL DALAM MEMBANGUN KERUKUNAN UMAT BERAGAMA DI DESA WOLOGAI, KABUPATEN ENDE, NUSA TENGGARA TIMUR - Rizalman Ndata; Mukayat Al Amin; M. Febriyanto Firman Wijaya (Jurnal Ilmiah Sosiologi Agama (JISA), 2026)
This study aims to analyze the role of the Gawi dance as local wisdom in fostering religious harmony in Wologai Village, Ende Regency, East Nusa Tenggara. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and documentation involving traditional leaders, religious leaders, and local community members selected purposively. Data analysis was conducted using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal that the Gawi dance functions not only as a cultural expression but also as a social mechanism that strengthens social cohesion. The practice of Gawi creates an inclusive social space, enhances trust, and builds interreligious social networks. From a social capital perspective, Gawi serves as a medium for producing bridging social capital that connects individuals from different backgrounds through shared collective experiences. Furthermore, this cultural practice gains religious legitimacy, allowing it to be widely accepted within the community. This study highlights that local wisdom has significant potential in promoting sustainable and context-based religious harmony. Therefore, empowering local cultural practices can serve as an alternative approach to maintaining social harmony at the community level.